PHOTOGRAPHY OF TIME - Coșniceru, Nicolae (Design/Arts/Culture, 2023)
Seeing the configuration of a place firsthand, we can believe that it has always been like that and we don’t ask ourselves questions about how it looked five years ago or 20 years ago and what processes and changes have taken place. It is possible that it was an unhealthy place and became a point of attraction where the community could spend time and carry out cultural or recreational activities, or it was a protected natural site and interventions beyond the limit of the law would have transformed it into an industrial, residential or commercial area, which led to overcrowding and pollution. Documentaries of the respective place taken at different times can help preserve local history and bring the community awareness of the recent history and the changes that have taken place. They will claim a lost inheritance if this is the case and if social promoters will campaign in this sense. But above all, they need to know the context in which they are. Because they were the object of my study or because I accidentally encountered places that had undergone significant changes and had previous documentation, I proposed to provide documents of organic changes or actions that must be under the lens of criticism. I am motivated by the need to draw attention to the worrying aspects of everyday life, before being too late for public reactions. In a country with a fragile democracy where the authorities do not hear the voice of civil society, I want to bring to the public conscience the negative aspects that are happening here and now, which can have significant implications for the present and future of the population.